Os caciques Ñheçu e Sepé Tiaraju – o mau e o bom selvagem às vistas da literatura e da história - Hamermüller, Genaro Luíz (2018)
This research aims to study the historical and literary representations built about Ñheçu and Sepé Tiaraju caciques, that lived between the 17th and the 18th century, and how those views increased the ideas that characterized the good and the bad savage, through a European perspective. We also analyzed how the said writings reproduced and merged themselves into another authors' works, disseminating domination ideologies. We verified socio-political elements through the religion diffusion proposed by Companhia de Jesus and the effects to the guarani culture, we also verified factors studied by Eco (2012), about the author-work-reader and concepts like decolonialism and medieval imaginary. The works chosen as corpus for the investigation are: Os Três Mártires Rio-Grandenses, from the priest Luís Gonzaga Jaeger S. J. (1951); the epic poem O Uraguai, from Basílio da Gama (1769); the work Sepé Tiaraju - Uma farsa em nossa história, from Ubirajara Raffo Constant (2006) ant the theorical essay Terra de Ñheçu, from the writer Nelson Hoffmann (2009). This investigation proposal signalizes to the qualitative research field; the theoretical basis is the comparative literature from authors like Coutinho and Carvalhal (1994) and Santiago (2000). It was important, to this research, the analysis from scholars like Anibal Quijano (2005), that deciphered aspects relating to the power coloniality; Walter Mignolo (2003) and Gayatri C. Spivak (2014), that based this research about the questions related to decoloniality and subalternity; Erneldo Schallemberger (2006), which talk about the guarani territoriality; and Laura de Mello e Souza (1986), that discuss the respect to medieval imaginary in her works. We can note that, nowadays, this representation about all and any indigenous is still made naturally; for this reason, we understand that this study could contribute to the reversion of this value judgement, in the sense of recognize that in these representations there is almost always present only the colonizers' voice. By using the polyphony and dialogism concepts, in the Bakhtin (2010) perspective, and the comparative literature methodology, we find out, in the corpus works, that the winners voice become present, promoting prejudice by disseminating a colonized thought. Therefore, we understand that creation of historical and literary characters, as Ñheçu and Sepé, thus represented, helped to ideologically structure the projection of Portugal and Spain colonialist imperialism, apart from the ideologies coming from the Religious Counter-Reformation, sowing conservative ideals, good practice and politeness in conformity with the religious and Eurocentric precepts to represent the good and the bad savage.